2021
DOI: 10.1111/appy.12475
|View full text |Cite
|
Sign up to set email alerts
|

Mental health literacy: A systematic review of knowledge and beliefs about mental disorders in Malaysia

Abstract: Mental health literacy: A systematic review of knowledge and beliefs about mental disorders in Malaysia (2021) Asia-Pacific Psychiatry, . Cited 2 times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 87 publications
3
15
0
1
Order By: Relevance
“…This study reported that those who have good social support have 1.4 times mental health literacy than those who have poor social support which is similar with a study conducted in Malaysia [24]. Similar ndings were reported among the community in Thailand and China, wherein signi cant negative correlation was reported between MHL and loneliness [25,26] In addition, to the above factors being signi cant determinants of MHL, this study also reported a signi cant association between smoking and alcohol consumption with MHL.…”
Section: P -Value<025supporting
confidence: 88%
See 1 more Smart Citation
“…This study reported that those who have good social support have 1.4 times mental health literacy than those who have poor social support which is similar with a study conducted in Malaysia [24]. Similar ndings were reported among the community in Thailand and China, wherein signi cant negative correlation was reported between MHL and loneliness [25,26] In addition, to the above factors being signi cant determinants of MHL, this study also reported a signi cant association between smoking and alcohol consumption with MHL.…”
Section: P -Value<025supporting
confidence: 88%
“…Similar ndings were reported among the community in Thailand and China, wherein signi cant negative correlation was reported between MHL and loneliness [25,26] In addition, to the above factors being signi cant determinants of MHL, this study also reported a signi cant association between smoking and alcohol consumption with MHL. Interestingly, we found that individuals who did not smoke or consume alcohol tended to have higher MHL levels than that of smokers & alcohol consumers which is similar with the study conduct in Malaysia [24].…”
Section: P -Value<025supporting
confidence: 87%
“…In Malaysia, low levels of MHL have been reported among young adolescents, wherein only a minority (3%) of adolescents were classified as having adequate MHL (i.e., the ability to correctly recognize mental health disorders alongside having the intention to seek help) [ 17 ]. More concerning is that adolescents with low levels of MHL have an increased risk of developing mental health disorders [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of cultural competence, according to Zarzycka et al, are cultural awareness, knowledge, sensitivity, skills, competence, and dynamics [ 3 ]. These variables affect the health literacy of members of the same ethnic group, health behaviors, perceived risk, attitudes, and beliefs towards health care [ 4 ]. Therefore, several studies argue that to ensure effective and culturally adequate care and to develop culturally competent health care practices, properly educated providers are required [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%